2013
DOI: 10.1186/1546-0096-11-35
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies in children and young adults on etanercept: summary of cases from clinical trials and post marketing reports

Abstract: BackgroundMalignancy risk may be increased in chronic inflammatory conditions that are mediated by tumor necrosis factor (TNF), such as juvenile idiopathic arthritis (JIA), but the role of TNF in human cancer biology is unclear. In response to a 2011 United States Food & Drug Administration requirement of TNF blocker manufacturers, we evaluated reporting rates of all malignancies in patients ≤30 years old who received the TNF blocker etanercept.MethodsAll malignancies in etanercept-exposed patients aged ≤30 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
1
8
0
2
Order By: Relevance
“…These results are in line with several previous studies that either found no increased incidence of malignancies in JIA patients [ 13 15 ] or an increased risk for cancer independent of TNF-α-treatment [ 1 , 16 20 ]. However, some studies suggested that new therapeutics might be responsible for an increased risk of cancer in JIA patients [ 13 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with several previous studies that either found no increased incidence of malignancies in JIA patients [ 13 15 ] or an increased risk for cancer independent of TNF-α-treatment [ 1 , 16 20 ]. However, some studies suggested that new therapeutics might be responsible for an increased risk of cancer in JIA patients [ 13 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…After screening all participants with including and excluding criteria, 201 patients were selected, randomly and evenly assigned in three groups: ETA (receiving 50 mg of etanercept twice weekly, etanercept was purchased from Amgen, Thousand Oaks, USA) (Hooper et al 2013) as a control group, ETABJ (receiving 50 mg of etanercept twice weekly, 50 ml blueberry juice daily) as a blueberry plus group and ETAPJ (matched etanercept and placebo juice) as a blueberry minus group. Since fifty ml blueberry juice was used for each patient (more than 50 kg) in an experimental group daily, the concentration of used blueberry juice was less than 0.1% (v/w).…”
Section: Methodsmentioning
confidence: 99%
“…Hooper et al 66 conducted a review on malignancies in children and young adults exposed to etanercept using the Amgen clinical trial database and postmarketing global safety database. For the 0- to 17-year age group, the reported rate appeared higher than incidence rates from a general pediatric population of similar ages and was primarily due to an increase in Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%